Heavy reliance on carbohydrate across a wide range of exercise intensities during voluntary arm ergometry in persons with paraplegia - Jacobs, Kevin A. (Maney Publishing, 2013)
CONTEXT/OBJECTIVE: To describe and compare substrate oxidation and partitioning during voluntary arm ergometry in individuals with paraplegia and non-disabled individuals over a wide range of exercise intensities. DESIGN: Cross-sectional study. SETTING: Clinical research facility. PARTICIPANTS: Ten apparently healthy, sedentary men with paraplegia and seven healthy, non-disabled subjects. INTERVENTIONS: Rest and continuous progressive voluntary arm ergometry between 30 and 80% of peak aerobic capacity (VO(2peak)). OUTCOME MEASURES: Total energy expenditure and whole body rates of fat and carbohydrate oxidation. RESULTS: A maximal whole body fat oxidation (WBFO) rate of 0.13 ± 0.07 g/minute was reached at 41 ± 9% VO(2peak) for subjects with paraplegia, although carbohydrate became the predominant fuel source during exercise exceeding an intensity of 30–40% VO(2peak). Both the maximal WBFO rate (0.06 ± 0.04 g/minute) and the intensity at which it occurred (13 ± 3% VO(2peak)) were significantly lower for the non-disabled subjects than those with paraplegia. CONCLUSION: Sedentary individuals with paraplegia are more capable of oxidizing fat during voluntary arm ergometry than non-disabled individuals perhaps due to local adaptations of upper body skeletal muscle used for daily locomotion. However, carbohydrate is the predominant fuel source oxidized across a wide range of intensities during voluntary arm ergometry in those with paraplegia, while WBFO is limited and maximally achieved at low exercise intensities compared to that achieved by able-bodied individuals during leg ergometry. These findings may partially explain the diminished rates of fat loss imposed by acute bouts of physical activity in those with paraplegia.